DISABILITY AND TOURISM IN NINETEENTH- ANDTWENTIETH-CENTURY ITALY - Maffi, Luciano; Fagnani, Martino Lorenzo, 1989- ([S.l.] : ROUTLEDGE, 2021)
Attention to the issue of disabilities has intensified in recent decades, prompting States and organizations to respond with appropriate measures to promote inclusion of persons with disabilities in all social environments. This book's thesis is that the seeds of this inclusivity were planted by the development of tourism for people with disabilities in the nineteenth and twentieth centuries. The book explores the development of tourism for people with disabilities in Italy during this time period. It adds an important tessera to the mosaic of international literature that has rarely considered the history of tourism and the history of disabilities in a unified manner. While certainly of great interest to an Italian audience, the discussion of the various responses taking form in Italy to the needs of persons with disabilities, and the role these responses have played in the development of mass tourism generally, is also quite pertinent to international contexts. This book is based largely on unpublished sources. The authors' hope is that the presentation of these new materials combined with the innovative approach of a historical study of tourism through the lens of disabilities will open up international scholarly debate and discussion drawing in contributions from all disciplines.
OCLC-licensed vendor bibliographic record.
Keywords: HISTORY / Europe / Italy; HISTORY / Modern / 19th Century; HISTORY / Modern / 20th Century; Tourism -- Italy -- History -- 19th century; Tourism -- Italy -- History -- 20th century; People with disabilities -- Travel -- Italy